أساس الحصانة الدبلوماسية في القانون الدولي مقارنة بالفقه الإسلامي (El-Wahat Journal for Research and Studies, 2023)
ملخص:تهدف الدراسة إلى إبراز النظريات التي يستند عليها القانون الدولي لتبرير الحصانة الدبلوماسية، والانتقادات الموجهة إليها، نظرا لتغير الظروف وتطور المفاهيم والممارسات الدولية الحديثة، مع المقارنة بأحكام الفقه الإسلامي والقواعد المستمدة من الكتاب والسنة النبوية، وما جرى عليه التطبيق في الدولة الإسلامية كمنح عقد الأمان للرسل والسفراء، ما جعلهم يتمتعون بحصانات وامتيازات خاصة. واستعملت في ذلك المنهج المقارن لبيان أوجه الاتفاق والاختلاف بين القانون الدولي والفقه الإسلامي.وخلصت الدراسة إلى عدة نتائج، أهمها:-        أسبقية الإسلام في تنظيم العلاقات الدولية وما يتعلق بها من حصانات الرسل والسفراء.-        توافق عقد الأمان في الفقه الإسلامي كأساس للحصانة الدبلوماسية مع نظرية مقتضيات الوظيفة إلى حد بعيد.-        اتفاق كبير بين قواعد القانون الدولي وأحكام الشريعة الإسلامية فيما يخص الحصانة الشخصية والامتيازات المالية، وحصانة المقر.-        اختلاف ظاهر بينهما فيما يتعلق بالحصانة القضائية المدنية والجنائية، وواجب أداء الشهادة.كلمات دالة: حصانة، مبعوث دبلوماسي، رسول، مستأمن، قانون دولي، شريعة إسلامية، عقد أمان.Abstract:The study aims to highlight the theories on which international law is based to justify diplomatic immunity, and criticism directed at it, due to changing circumstances and development of modern international concepts and practices, compared with Islamic jurisprudence rulings and the rules derived from Quran and Sunnah, and what was implemented in Islamic States, as granting security contract to messengers and ambassadors, what made them had special immunities and privileges.And i used the comparative approach to show the points of agreement and differences between international law and Islamic jurisprudence.The most important results of the study:-         Islam’s primacy in regulation of international relations and immunities related to messengers and ambassadors.-         The safety contract in Islamic jurisprudence as a basis for diplomatic immunity identical with job requirements theory.-         A large agreement between international law rules and provisions of Islamic law with regard to personal immunity, financial privileges, and headquarters immunity.-         An apparent difference between them regarding civil and criminal judicial immunity, and the obligation to testify. Key words: Diplomacy, the envoy, the messenger, international law, Islamic law.